The presence of black vultures at the calving sites and its effects on cows' and calves' behaviour immediately following parturition - Toledo, L. M.; Paranhos Da Costa, M. J R [UNESP]; Schmidek, A.; Jung, J.; Ciryllo, J. N S G; Cromberg, V. U. (Elsevier, 2013)
Black vultures (Coragyps atratus) are often present near calving sites, and under this situation they may play a positive role by removing animal carcasses and afterbirth or a negative role by attacking neonate calves or disturbing cow-calf behaviours following parturition. Cow-calf behaviour was recorded over a 4-year study period from a total of 300 births involving 200 Nellore, 54 Guzerat, 20 Gyr and 26 Caracu cows. The calving site in relation to the location of the herd, considering cow-calf pairs within, close or distant to the herd, the presence of vultures and the behaviour of cows and calves were recorded instantaneously, at 5-min interval. On average, vultures were present at 80% of the calving sites. The frequency of vultures present at calving sites was dependent on the years for the Nellore herd, increasing from 1998 to 2003. When vultures were present, the time that the cow was in contact with its calf decreased, and the percentage of time that the cow was standing still increased. Vultures were observed pecking cows and their neonates during 34.1% of all recordings. However, in only two cases pecking injuries were actually observed on calves that were noted to be very weak. The preliminary results suggest that although black vultures cannot be characterized as a predator of neonate calves, they sometimes attack neonate calves and their presence near the calving sites alter the behaviours of cows and calves. © 2012 The Animal Consortium.
Keywords: birth; black vulture; cattle; coragyps atratus; first suckling; animal; animal behavior; bird; Brazil; comparative study; female; maternal behavior; newborn; observation; physiology; predation; statistical model; Animals; Animals, Newborn; Behavior, Animal; Birds; Cattle; Female; Logistic Models; Maternal Behavior; Observation; Predatory Behavior